1995
DOI: 10.1111/j.1651-2227.1995.tb13814.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperimmune cow colostrum reduces diarrhoea due to rotavirus: a double‐blind, controlled clinical trial

Abstract: The therapeutic efficacy of hyperimmune bovine colostrum (HBC) from cows immunized with four serotypes of human rotavirus was evaluated in a double-blind, randomized trial in 75 boys, aged 6-24 months, infected with rotavirus diarrhoea. The treatment group received 100 ml of HBC three times a day for 3 consecutive days, while the controls received the same amount of bovine colostrum from significantly shorter duration of diarrhoea than the controls (median 56 versus 72 h (p<0.001); confidence interval of media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(40 citation statements)
references
References 28 publications
2
36
0
Order By: Relevance
“…8,9 Our study shows that recovery time and length of hospital stay were shorther in the treatment group. Similar results were reported by Ylitalo et al 8 12 in Bangladesh in which oral hyperimune bovine colostrum was effective to accelerate the recovery time and the length of hospital stay for acute diarrhea caused by rotavirus in infants and children compared with control of 56 hours compared to 72 hours. Guarino et al, 13 in Italy found the length of hospital stay was 76 hours in the group of acute diarrhea caused by rotavirus given antiviral human serum immunoglobulin compared to 131 hours in control group.…”
Section: Discussionsupporting
confidence: 78%
“…8,9 Our study shows that recovery time and length of hospital stay were shorther in the treatment group. Similar results were reported by Ylitalo et al 8 12 in Bangladesh in which oral hyperimune bovine colostrum was effective to accelerate the recovery time and the length of hospital stay for acute diarrhea caused by rotavirus in infants and children compared with control of 56 hours compared to 72 hours. Guarino et al, 13 in Italy found the length of hospital stay was 76 hours in the group of acute diarrhea caused by rotavirus given antiviral human serum immunoglobulin compared to 131 hours in control group.…”
Section: Discussionsupporting
confidence: 78%
“…[7][8][9] Hyperimmune bovine colostrum from cows immunised with human rotavirus has been shown to reduce the duration and severity of childhood diarrhoea due to rotavirus. 10 A rotavirus vaccine was fi rst licensed in 1998, but was withdrawn after less than 1 year of use because of risk of intussusception. Two new vaccines have been or will soon be licensed and could be available in the next 2-3 years.…”
Section: Introductionmentioning
confidence: 99%
“…Bovine antibodies have also been applied therapeutically, resulting in a significant reduction in diarrhea in rotavirus-infected children treated with antibodies isolated from colostrum produced by cows immunized against several strains of human rotavirus. 14 The evaluation of bovine colostrum antibodies against Cryptosporidium parvum,…”
Section: Milk Immunoglobulinsmentioning
confidence: 99%